English Lecturers’ Preferences for High Impact Professional Development in Indonesia - Syafitri, Winda (Association of Language Teachers in Southeast Asia (ALTSA), 2018)
Professional development plays an important role in improving both teachersÃ¢â‚¬â„¢ and studentsÃ¢â‚¬â„¢ outcomes. With various models and strategies, professional development is expected to have a high impact on teaching learning success. This study focused on English lecturersÃ¢â‚¬â„¢ preferences for high impact professional development in Indonesia. With small survey design, the data were collected from 20 English lecturers around Indonesia by using questionnaire and interview. This research reveals that most of English lecturers in Indonesia expressed that they prefer seminar, conference, workshop, training, and action research to others because of their short durations and their high impacts. Then, related to technology, they said that internet helps them very much in preparing better instruction, but not in developing their professionalism. The result of this study would be very useful for government and stakeholder to take any decision related to English lecturersÃ¢â‚¬â„¢ professional development.Keywords: Professional Development Preferences, High ImpactÃ‚Â